Investigation into the wake aerodynamics of a five-straight-bladed vertical axis wind turbine by wind tunnel tests. Issue 155 (August 2016) - Peng, H.Y.; Lam, H.F.; Lee, C.F.
Abstract: Wake characteristics have significant effects on the performance design of standalone turbines and the optimal placement of multiple turbines. In the literature to date, little experimentation has been done on the wake of vertical axis wind turbines (VAWTs), and understanding of such wake is far from adequate. In this work, systematic measurements are presented of both the near and mid-range wake of a five-straight-bladed VAWT in a wind tunnel. The blockage ratio of the VAWT was 1.8%, and no correction of the measured data was required. The wake flow fields were measured up to 10 turbine diameters (10 D ) to the downstream. The wake exhibited high asymmetry in the horizontal direction. In addition, the wake expanded more in the horizontal direction than in the vertical direction. The causes of the asymmetry were analyzed and discussed through the experimental results. An engineering wake model was proposed to characterize the wake edges and the average velocities. The existence of a pair of counter-rotating vortical structures in the wake was detected. Moreover, the integral length scale was found to steadily grow with the downstream distance. This work contributes to the knowledge of the VAWTs׳ wake and the application of VAWTs in wind farm layout design. Highlights: Systematic measurement of the near and mid-range wake of a five-bladed VAWT. Finding of the horizontal wake asymmetry and analysis of the causes. Study of the integral length scales downstream and analysis of their evolutions. Construction of an engineering model characterizing the wake edges and velocities. Detection of the existence of the counter-rotating vortical structures downstream.